The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fneur.2019.00598
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sex and Adaptation on Migraine Frequency and Perceived Stress: A Cross-Sectional Case-Control Study

Abstract: Background: Perceived stress has been related to migraine. The relationship between sex, migraine frequency, and severity of perceived stress remains unclear. We investigated perceived stress among migraineurs. Methods: This cross-sectional case-control study involved 577 clinical outpatients at a tertiary hospital in Taiwan. Demographic and clinical data, including migraine characteristics, were collected. Migraineurs were stratified by episode frequency, aura and sex, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…Other studies also reported that women had higher stress sensitivity and a higher risk for depression and anxiety compared to men with ocular prostheses. [ 9 , 22 , 23 ] Moreover, gender was the only factor significantly associated with somatization scores in this study, suggesting female patients appeared to somatic more. The reason may lie in that women patients are less likely to accept their current condition and responded negatively to their overall situations, thus leading to somatic complaints.…”
Section: Discussionmentioning
confidence: 51%
“…Other studies also reported that women had higher stress sensitivity and a higher risk for depression and anxiety compared to men with ocular prostheses. [ 9 , 22 , 23 ] Moreover, gender was the only factor significantly associated with somatization scores in this study, suggesting female patients appeared to somatic more. The reason may lie in that women patients are less likely to accept their current condition and responded negatively to their overall situations, thus leading to somatic complaints.…”
Section: Discussionmentioning
confidence: 51%
“…Similarly, several observational studies demonstrate an association between stress and migraine symptom burden. Higher migraine frequency is associated with higher levels of perceived stress [ 40 ]. High job strain, resulting in lack of time for personal care and leisure, is associated with an increased odds of migraine [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies on stress adaptation in migraine patients are limited, yet perceived stress was reported to be higher in migraine patients with increased frequency of attacks (23). No signi cant difference was found in the 'Upset because of something that happened unexpectedly' subgroup in the perceived stress scale when patients with migraine were compared with the control group, while other subgroup scores were signi cantly higher in migraineurs (23). These results are in line with our data and support that the reaction to extraordinary, unexpected, and alarming stress could be different in migraine patients.…”
Section: Discussionmentioning
confidence: 99%